Solitary intraventricular Hodgkin lymphoma post-transplant lymphoproliferative disease (HL-PTLD): Case report. (November 2019) - Azriel, Amit; Towner, James E.; Gaillard, Frank; Box, Georgia; Rogers, TeWhiti; Morokoff, Andrew
Highlights: Lymphomas affecting the central nervous system (CNS) are uncommon malignancies. Post-transplant lymphoproliferative disease (PTLD) is a complication of organ transplantation. CNS involvement in PTLD is rare, and the majority of these cases are PCNSL. Hodgkin lymphoma PTLD (HL-PTLD) constitutes a very small percentage of PTLD. Abstract: Lymphomas affecting the central nervous system (CNS), both primarily and secondarily, are uncommon malignancies. Immunosuppressed states, including iatrogenic immunosuppression following organ transplantation, are the most significant risk factors for developing primary CNS lymphoma (PCNSL). Post-transplant lymphoproliferative disease (PTLD) is a well described complication following bone marrow or solid organ transplantation. PTLD is usually a systemic disease with occasional CNS involvement. The incidence of CNS involvement in PTLD is low, and the majority of these cases tend to be PCNSL. Hodgkin lymphoma PTLD (HL-PTLD) constitutes only a very small percentage of PTLD. We report a rare case of a primary intraventricular CNS classical HL-PTLD in a male patient, 18 years following renal transplantation. The location allowed for safe neurosurgical intervention which resolved the symptom of elevated intracranial pressure and allowed for induction of a Rituximab-based chemotherapy regimen. Both the ventricular location of the PTLD and Hodgkin Lymphoma PTLD are themselves individually quite rare and have not previously been reported together. The unique location allowed safe neurosurgical intervention which quickly resolved the symptom of elevated intracranial pressure and allowed for induction of a Rituximab-based chemotherapy regimen.